MODEL MANAJEMEN PERSEDIAAN KAITANNYA DENGAN EFEKTIFITAS DAN EFISIENSI BAGI PERUSAHAAN ( Kajian teoritis ) - Ni Kadek Noviyanti (STIE BIITM, 2020)
AbstractGood inventory management is the key to success for every company, both companiesengaged in industry and trading companies. Managing inventory properly can make itpossible to use resources optimally and efficiently. Inventory is the main part of workingcapital, because it is the biggest investment in the production process or in other companies,therefore it is necessary to use a way to namely the current inventory model which is oftenfound one of them with the EOQ model (Economic Order Quantity), with a case. The problemlater is how to determine the supply of materials using EOQ, and how much the difference incosts occur with the EOQ model. The goal of all companies is to maximize the value of thecompany both economically and socially, from the case and discussion it turns out andproven that the EOQ model can be effective and efficient in the company.